CCCH Zinc finger genes in Barley: genome-wide identification, evolution, expression and haplotype analysis - Qi Ai; Wenqiu Pan; Yan Zeng; Yihan Li; Licao Cui (BMC Plant Biology, 2022)
Abstract Background CCCH transcription factors are important zinc finger transcription factors involved in the response to biotic and abiotic stress and physiological and developmental processes. Barley (Hordeum vulgare) is an agriculturally important cereal crop with multiple uses, such as brewing production, animal feed, and human food. The identification and assessment of new functional genes are important for the molecular breeding of barley. Results In this study, a total of 53 protein-encoding CCCH genes unevenly dispersed on seven different chromosomes were identified in barley. Phylogenetic analysis categorized the barley CCCH genes (HvC3Hs) into eleven subfamilies according to their distinct features, and this classification was supported by intron–exon structure and conserved motif analysis. Both segmental and tandem duplication contributed to the expansion of CCCH gene family in barley. Genetic variation of HvC3Hs was characterized using publicly available exome-capture sequencing datasets. Clear genetic divergence was observed between wild and landrace barley populations in HvC3H genes. For most HvC3Hs, nucleotide diversity and the number of haplotype polymorphisms decreased during barley domestication. Furthermore, the HvC3H genes displayed distinct expression profiles for different developmental processes and in response to various types of stresses. The HvC3H1, HvC3H2 and HvC3H13 of arginine-rich tandem CCCH zinc finger (RR-TZF) genes were significantly induced by multiple types of abiotic stress and/or phytohormone treatment, which might make them as excellent targets for the molecular breeding of barley. Conclusions Overall, our study provides a comprehensive characterization of barley CCCH transcription factors, their diversity, and their biological functions.